Literatura e cinema: interseções - Vera Lúcia Follain de Figueiredo (Estudos de Literatura Brasileira Contemporânea, 2011)
Literature and cinema: intersections Vera Lúcia Follain de Figueiredo This article will focus on intersections and convergences motivated by market mediation in the field of cultural assets and technological advances that indicate a change of the position of literature in the cultural hierarchy. For this reason, it is questioned the eventual effects of the expansion of audio-visual means on the production, consumption and valuation agendas of literature works.